Comparison of rubella seroepidemiology in 17 countries: progress towards international disease control targets - Anthony Nardone; Annedore Tischer; Nick Andrews; Jo Backhouse; Heidi Theeten; Nina Gatcheva; Marios Zarvou; Bohumir Kriz; Richard G Pebody; Kalman Bartha; Darina O'Flanagan; Dani Cohen; et al. (The World Health Organization, 2008)
OBJECTIVE: To standardize serological surveillance to compare rubella susceptibility in Australia and 16 European countries, and measure progress towards international disease-control targets. METHODS: Between 1996 and 2004, representative serum banks were established in 17 countries by collecting residual sera or community sampling. Serum banks were tested in each country and assay results were standardized. With a questionnaire, we collected information on current and past rubella vaccination programmes in each country. The percentage of seronegative (< 4 IU/ml) children (2-14 years of age) was used to evaluate rubella susceptibility, and countries were classified by seronegativity as group I (< 5%), group II (5-10%) or group III (> 10%). The proportion of women of childbearing age without rubella protection (< 10 IU/ml) was calculated and compared with WHO targets of < 5%. FINDINGS: Only Romania had no rubella immunization programme at the time of the survey; the remaining countries had a two-dose childhood schedule using the measles, mumps and rubella (MMR) vaccine. The percentage of susceptible children defined five countries as group I, seven as group II and four as group III. Women of childbearing age without rubella protection were < 5% in only five countries. CONCLUSION: Despite the low reported incidence in many countries, strengthening the coverage of the routine two-dose of MMR vaccine among children is needed, especially in group III countries. Catch-up campaigns in older age groups and selective targeting of older females are needed in many countries to ensure necessary levels of protective immunity among women of childbearing age.